Marek’s disease virus infection alters the composition of exosomes in chicken fibroblasts and promotes viral replication - Cuiping Song; Wenjing Yang; Jiepeng Wu; Xusheng Qiu; Lei Tan; Yingjie Sun; Ning Tang; Yang Qu; Ying Liao; Chan Ding (Veterinary Microbiology, 2026)

Metabarcoding Chironomid Pupal Exuviae Enables Scalable Biomonitoring With High Comparability to Morphotaxonomy - Wu Han; Chu‐Ming Zhang; Cheng Qian; Tsz‐Ying Chan; Thilina S. Nimalrathna; Bai‐an Lin; Xiao‐Long Lin; Hong‐Qu Tang; Peter S. Cranston; Mathew Seymour (Molecular Ecology, 2026)
Conventional morphotaxonomy‐based biomonitoring requires modernization to enable timely assessments in the face of an accelerating freshwater biodiversity crisis. The Chironomid Pupal Exuviae Technique (CPET) is an established biomonitoring approach with considerable potential for integration with molecular methods, as the shed pupal skins of emerging adults provide a source of DNA. We tested the performance of DNA metabarcoding for detecting species richness, recovering beta‐diversity patterns and assessing biodiversity responses to environmental gradients using 15 mock communities and 12 natural chironomid pupal exuviae samples collected from Hong Kong streams. Additionally, the effects of primer choice were assessed by comparing a chironomid‐specific primer set (COI‐S) against a universal, highly degenerate primer set (COI‐V). Our results show that both primer sets achieved high species detection rates in mock communities (86% and 84%, respectively) and consistently recovered predefined community dissimilarities. In natural community samples, however, only COI‐S produced beta‐diversity patterns significantly congruent with that of the morphological dataset (Procrustes r = 0.74, p = 0.003). Both metabarcoding datasets effectively captured seasonal community shifts and demonstrated greater sensitivity to environmental gradients than traditional morphological identification. Notably, the COI‐S dataset explained the highest proportion of community variation (adjusted R 2 = 44.3%), along the environmental gradient, outperforming both the morphotaxonomy (32.5%) and the COI‐V (29.0%) analyses. Here we propose Meta‐CPET, an integrated framework that combines the ecological relevance of CPET with the efficiency, scalability, and resolution of DNA metabarcoding. Our findings show that bulk‐sample metabarcoding enables practical, standardized and large‐scale freshwater biomonitoring while maintaining strong comparability with conventional methods.

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Dynamic WNT signaling controls differentiation of hematopoietic progenitor cells from human pluripotent stem cells - Mo Li; Keiichiro Suzuki; Mengge Wang; Christopher Benner; Manching Ku; Li Ma; Ladan Kobari; Na Young Kim; Nuria Montserrat; Chan-Jung Chang; Guanghui Liu; Jing Qu; et al. (Science China Life Sciences, 2025)

Multi-omics profiling reveals infectious bursal disease virus-induced alterations in gene expression and metabolism in chicken bursa of fabricius - Cuiping Song; Siyu Li; Yanmei Yuan; Wei Gao; Xusheng Qiu; Lei Tan; Yingjie Sun; Ning Tang; Yang Qu; Ying Liao; Chan Ding (Veterinary Microbiology, 2025)

Microbial diversity, functional properties, and flavor characteristics of high-temperature Daqu with different colors - Zhendong Zhang; Xiaoxu Ran; Zhuang Guo; Qiangchuan Hou; Dingwu Qu; Chan Wang; Yuanyuan Xu; Yurong Wang (Food Research International, 2025)

Corrigendum to ‘Personal exposure monitoring of fine and coarse particulate matter using exposure assessment models for elderly residents in Hong Kong’ [Chemosphere 357 (June 2024) 141975] - Ka Hei Lui; Tianhang Zhang; Chung Ling Man; Chi Shing Chan; Steven Sai Hang Ho; Linli Qu; Helen Hoi Ling Kwok; Timothy Chi Yui Kwok; Kin Fai Ho (Chemosphere, 2024)

Microscopic and spectroscopic analysis of atmospheric iron-containing single particles in Lhasa, Tibet - Junyu Chen; Daobin Zhang; Yiran Fu; Jinhu Wang; Xiaomei Cui; Ci-ren Qu-zong; Qiangying Zhang; Chan Jin; Bu Duo (Journal of Environmental Sciences, 2024)

Personal exposure monitoring of fine and coarse particulate matter using exposure assessment models for elderly residents in Hong Kong - Ka Hei Lui; Tianhang Zhang; Chung Ling Man; Chi Shing Chan; Steven Sai Hang Ho; Linli Qu; Helen Hoi Ling Kwok; Timothy Chi Yui Kwok; Kin Fai Ho (Chemosphere, 2024)

MFENet: Multi-scale feature extraction network for images deblurring and segmentation of swinging wolfberry branch - Zhenwei Xing; Yutan Wang; Aili Qu; Chan Yang (Computers and Electronics in Agriculture, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Exploring the Wenchuan earthquake fault through the accurate location of WFSD-4# Well using seismic reflection - Yang-Yang Feng; Chang-Qing Yu; Hai-Bing Li; Chen Qu; Chan Wu; Qi Wang; Su Luo; Jin-Peng Huang; Ghazi Rehana (Applied Geophysics, 2022)

Particle size shapes the prokaryotic microbial communities in mangrove sediments: A case study of Sanya, China - Wu Qu; Michael Vicent Shija; Jie Wu; Min Jin; Jianxin Wang; Runying Zeng; Zhuhua Chan (Acta Oceanologica Sinica, 2022)

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

The LXR ligand GW3965 inhibits Newcastle disease virus infection by affecting cholesterol homeostasis - Xiang-xiang Sheng; Ying-jie Sun; Yuan Zhan; Yu-rong Qu; Hua-xia Wang; Miao Luo; Ying Liao; Xu-sheng Qiu; Chan Ding; Hong-jie Fan; Xiang Mao (Archives of Virology, 2016)

A genome-wide association study for colorectal cancer identifies a risk locus in 14q23.1 - Mathieu Lemire; Conghui Qu; Lenora W. M. Loo; Syed H. E. Zaidi; Hansong Wang; Sonja I. Berndt; Stéphane Bézieau; Hermann Brenner; Peter T. Campbell; Andrew T. Chan; Jenny Chang-Claude; Mengmeng Du; et al. (Human Genetics, 2015)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Background exposure of urban populations to lead and cadmium: comparison between China and Japan - Y.-Q. Wu; Zuo-Wen Zhang; Chan-Seok Moon; Shinichro Shimbo; Takao Watanabe; Feng-Sheng He; Shun-Fu Zhou; Jiang-Bin Qu; M. Ikeda; De-Ming Su (International Archives of Occupational and Environmental Health, 1997)